RECENT TERMINOLOGICAL INNOVATIONS IN ENGLISH: THE ROLE OF GLOBALIZATION - Azimova Umida Kilich qizi (Western European Studies, 2025)
This article explores the influence of globalization on the English language, focusing on the recent emergence of new terminologies in various domains such as digital technologies, environmental discourse, work culture, and social media. These innovations reflect the language’s ability to adapt to global changes, demonstrating how the English language absorbs and modifies terms to remain relevant in contemporary communication. The study emphasizes the role of globalization in shaping the English lexicon and contributing to the evolving discourse of modern society.
Keywords: modern; discourse